Flexible Electronics: Fabrication and Ubiquitous Integration - Martinez, Ramses V. (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Flexible Electronics platforms are increasingly used in the fields of sensors, displays, and energy conversion with the ultimate goal of facilitating their ubiquitous integration in our daily lives. Some of the key advantages associated with flexible electronic platforms are: bendability, lightweight, elastic, conformally shaped, nonbreakable, roll-to-roll manufacturable, and large-area. To realize their full potential, however, it is necessary to develop new methods for the fabrication of multifunctional flexible electronics at a reduced cost and with an increased resistance to mechanical fatigue. Accordingly, this Special Issue seeks to showcase short communications, research papers, and review articles that focus on novel methodological development for the fabrication, and integration of flexible electronics in healthcare, environmental monitoring, displays and human-machine interactivity, robotics, communication and wireless networks, and energy conversion, management, and storage.